Guitar Training in Character Building Efforts to Improve Student Creativity at Paranada Music House - Muhammad Rifki; Udi Utomo; Wadiyo Wadiyo (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to analyze the impact of guitar training on character building and its contribution to improving students' creativity at Paranada Music House. This study is a qualitative study, using several approaches, namely sociology with Robert Hinkle's Action Theory to analyze social dynamics and interactions during training sessions, and Arthur Combs' Humanistic Theory to analyze the intrinsic meaning and personal significance of training for students. These theories become the scalpel in this study. The results show that structured guitar training at Paranada Music House significantly contributes to character development and increased creativity in students. The sociological approach reveals how group interactions and relationships between instructors and students create a supportive learning environment, while the humanistic perspective highlights the personal growth and self-actualization experienced by students. In conclusion, guitar training at Paranada Music House not only improves musical skills but also plays a vital role in the holistic development of students, preparing them for future creative endeavors.